2019
DOI: 10.1001/jamanetworkopen.2019.12352
|View full text |Cite
|
Sign up to set email alerts
|

Association of Total Daily Physical Activity and Fragmented Physical Activity With Mortality in Older Adults

Abstract: Key PointsQuestionIs the manner in which older adults accumulate physical activity throughout the day, beyond the total amount of physical activity, associated with their mortality risk?FindingsIn this cohort study of 548 well-functioning adults aged 65 years and older, more fragmentated physical activity, but not total daily activity, was associated with increased mortality risk.MeaningFragmented physical activity of bouts lasting less than 5 minutes may reveal compensatory changes resulting from impaired phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 42 publications
7
61
0
4
Order By: Relevance
“…Describing the pattern of physical activity using active-to-sedentary transition probability provides a potential way to objectively quantify physical activity by incorporating 3 important components of physical activity: the time spent in active phase, the time spent in sedentary behaviors, and the transition between them. Previous studies 10 , 11 , 31 demonstrated that a more fragmented physical activity pattern, quantified by active-to-sedentary transition probability, is associated with slower gait speed and longer time to finish a 400-m walk independent of the total amount of physical activity, and may be more associated with risk of mortality compared with total amount of physical activity. Our study showed that both mild hearing loss and moderate or greater hearing loss were associated with a more fragmented physical activity pattern among these younger old adults.…”
Section: Discussionmentioning
confidence: 99%
“…Describing the pattern of physical activity using active-to-sedentary transition probability provides a potential way to objectively quantify physical activity by incorporating 3 important components of physical activity: the time spent in active phase, the time spent in sedentary behaviors, and the transition between them. Previous studies 10 , 11 , 31 demonstrated that a more fragmented physical activity pattern, quantified by active-to-sedentary transition probability, is associated with slower gait speed and longer time to finish a 400-m walk independent of the total amount of physical activity, and may be more associated with risk of mortality compared with total amount of physical activity. Our study showed that both mild hearing loss and moderate or greater hearing loss were associated with a more fragmented physical activity pattern among these younger old adults.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have developed new analytic approaches for accelerometer data in an effort to not just measure total accumulation of PA/SB time but to detect patterns in the data. Several studies have investigated patterns based on lengths of uninterrupted intervals ("bouts") and/or degree of fragmentation of PA/SB [15,22,[51][52][53][54][55][56][57]. More relevant to the current investigation, studies have also described variations in the timing of sedentary time and PA time accumulation with respect to hour of the day and/or day of the week, including differences in timing by sociodemographic factors [23,28,[58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential as we strive to assess the physical activity of particular subjects, like the frail population in clinical practice. Recently, Wanigatunga et al [ 51 ] proposed that highly irregular habits of physical exercise might be an early indication of reduced ability culminating in premature mortality. To this end, recording the fragmentation of physical activity is a critical phenotypic predictor for the degradation in free-living patterns in physical activity correlated with mortality.…”
Section: Discussionmentioning
confidence: 99%